2013
DOI: 10.1177/1541931213571217
|View full text |Cite
|
Sign up to set email alerts
|

Powered Ambulance Cots

Abstract: An experiment was conducted in order to examine the effect of differences in the design of two powered ambulance cots on operators. Experienced EMS workers performed two common tasks, loading and unloading the cots from a simulated ambulance bed. Dependent measures included muscle activity (trunk, shoulder, and arm muscles) and subjective perceptions. Independent variables were cot (Cot R and Cot Y), and weight on the cot (100, 150, and 200 lbs., to simulate patients of different weights). Muscle activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated the biomechanical stresses of loading a variety of stretchers and their effect on EMS work-place injuries. Sommerich et al found that powered stretchers drastically reduced muscle maximum voluntary exertions in the trunk and upper body during lifting and lowering activities [5]. Prairie et al found that powered stretchers alone were not enough to make the loading and unloading tasks safe, since one provider still had to bear the weight of the stretcher as it was taken in and out of the ambulance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the biomechanical stresses of loading a variety of stretchers and their effect on EMS work-place injuries. Sommerich et al found that powered stretchers drastically reduced muscle maximum voluntary exertions in the trunk and upper body during lifting and lowering activities [5]. Prairie et al found that powered stretchers alone were not enough to make the loading and unloading tasks safe, since one provider still had to bear the weight of the stretcher as it was taken in and out of the ambulance [6].…”
Section: Introductionmentioning
confidence: 99%